The Semantic Differential: A Device for Measuring the Interprofessional Communication of Selected Accounting Concepts - Oliver, Bruce L. (Journal of Accounting Research, 1974)
Bruce L. Oliver, The Semantic Differential: A Device for Measuring the Interprofessional Communication of Selected Accounting Concepts, Journal of Accounting Research, Vol. 12, No. 2 (Autumn, 1974), pp. 299-316